The Effect of Financial Knowlegde, Financial Attitude on Financial Management Behavior in Coffee Shop in Tangerang City - Reza Satria Aldiki; Dila Agustin; Desviera Zulfa (Universitas Mercu Buana, 2022)
The purpose of this study is to find out and how the influence of financial knowledge, financial attitudes on financial management behavior in coffee shop business actors in Tangerang City. The research design used in this study is a quantitative approach. The sampling technique used purposive sampling method. Methods of data collection using a questionnaire and obtained a sample of 31 respondents. In this study, researchers used descriptive data analysis techniques, regression tests and different t-tests with the help of the PLS software program. The results of data analysis and the results of the hypotheses in this study were tested with SmartPLS 3.0 and The results of this study are Financial Knowledge, and Financial Attitudes have no significant effect on the Financial Management Behavior of Coffee Shop Businesses in Tangerang City.